Chemical Preparation of Graphene Materials Results in Extensive Unintentional Doping with Heteroatoms and Metals. Issue 48 (5th October 2014) - Chua, Chun Kiang; Ambrosi, Adriano; Sofer, Zdeněk; Macková, Anna; Havránek, Vladimír; Tomandl, Ivo; Pumera, Martin
Abstract Chemical synthesis of graphene relies on the usage of various chemical reagents. The initial synthesis step, in which graphite is oxidized to graphite oxide, is achieved by a combination of chemical oxidants and acids. A subsequent chemical reduction step eliminates/reduces most oxygen functionalities to yield graphene. We demonstrate here that these chemical treatments significantly contaminate graphene with heteroatoms/metals, depending on the procedures followed. Contaminations with heteroatoms (N, B, Cl, S) or metals (Mn, Al) were present at relatively high concentrations (up to 3 at %), with their chemical states dependent on the procedures. Such unintentional contaminations (unwanted doping) during chemical synthesis are rarely anticipated and reported, although the heteroatoms/metals may alter the electronic and catalytic properties of graphene. In fact, the levels of unintentionally introduced contaminants on graphene are often higher than typical levels found on intentionally doped graphene. Our findings are important for scientists applying chemical methods to prepare graphene.